Evaluating the effectiveness of income generation projects in alleviating poverty in the rural communities of Ba-Phalaborwa Municipality - makaringe@webmail.co.za (University of Pretoria, 2013)
Dissertation (MSW (Social Development & Policy))--University of Pretoria, 2011.